2013
DOI: 10.1159/000353093
|View full text |Cite
|
Sign up to set email alerts
|

Close Relations between Podocyte Injuries and Membranous Proliferative Glomerulonephritis in Autoimmune Murine Models

Abstract: Background: Membranous proliferative glomerulonephritis (MPGN) is a major primary cause of chronic kidney disease (CKD). Podocyte injury is crucial in the pathogenesis of glomerular disease with proteinuria, leading to CKD. To assess podocyte injuries in MPGN, the pathological features of spontaneous murine models were analyzed. Methods: The autoimmune-prone mice strains BXSB/MpJ-Yaa and B6.MRL-(D1Mit202-D1Mit403) were used as the MPGN models, and BXSB/MpJ-Yaa+ and C57BL/6 were used as the respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 77 publications
1
22
0
Order By: Relevance
“…Interestingly, ACTN4 deficiency is also found in multiple human primary glomerulopathies including sporadic FSGS, minimal change disease, and IgA nephropathy (34 -37). Recent studies further indicated that the abundance of ACTN4 protein is significantly reduced in experimental glomerular diseases (38,39). Indeed, Actn4 knock-out mice do not survive the perinatal period, and the remaining mice that survive exhibit severe glomerular defects, podocyte injury, and proteinuria (40).…”
Section: Actn4 Is a Transcriptional Coactivator Of Nf-bmentioning
confidence: 99%
“…Interestingly, ACTN4 deficiency is also found in multiple human primary glomerulopathies including sporadic FSGS, minimal change disease, and IgA nephropathy (34 -37). Recent studies further indicated that the abundance of ACTN4 protein is significantly reduced in experimental glomerular diseases (38,39). Indeed, Actn4 knock-out mice do not survive the perinatal period, and the remaining mice that survive exhibit severe glomerular defects, podocyte injury, and proteinuria (40).…”
Section: Actn4 Is a Transcriptional Coactivator Of Nf-bmentioning
confidence: 99%
“…In our previous study, we observed infiltrating B cells in the glomerulus of male BXSB/MpJ-Yaa mice, although they were scarce in the lupus-prone B6.MRLc1 16 and female BXSB/MpJ mice. Therefore, we considered that the Yaa locus contributes to glomerular B-cell infiltration, leading to the severe MPGN in male BXSB/MpJ-Yaa mice.…”
Section: Discussionmentioning
confidence: 80%
“…20 We previously demonstrated that male BXSB/MpJ-Yaa mice at 3 months of age clearly show MPGN associated with glomerular IC depositions; no lesions were observed in females at the same age. 15,16 Therefore, the pathophysiology of the BXSB/MpJ-Yaa strain has been reported in males but not in females. The present study clarified that female BXSB/MpJ mice clearly develop autoantibody production and MPGN with mild albuminuria characterized by glomerular hypertrophy, increased mesangial cells and their matrix and thickening of GBM at 7 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction of the negative membrane charge in the glomerular filter has been observed, e.g., in diabetic nephropathy [28], in the nephrotic stage of IgA nephropathy [29], or in the rat model of puromycin induced nephrosis [30]. Consistent with a reduced negative charge of the podocyte cell surface, the expression of the sialo-and sulfoprotein podocalyxin (PODXL), the major contributor to the anionic surface charge of podocytes [31], respectively of the sialylation of PODXL is decreased in a variety of acquired human kidney diseases [32] and experimental nephropathy models [30,33,34]. To examine if NPs would in principle also be suitable for isolation of podocytes from mice with pathological glomerular alterations, the method was tested using transgenic mice of two established murine nephropathy models: GH-transgenic mice, a model of progressive glomerulosclerosis [35,36], and GIPR dn -transgenic mice, a model of diabetes mellitus associated nephropathy [16].…”
Section: Discussionmentioning
confidence: 99%